THE INFLUENCE OF INTELLECTUAL CAPITAL ON PROFITABILITY AND ITS IMPACT ON STOCK PRICE IN BANKING COMPANIES LISTED IN THE INDONESIA STOCK EXCHANGE - Loist, Christine (Asosiasi Dosen Akuntansi Indonesia, 2019)
The objective of the research was to find out and to analyze the influence of intellectual capital on stock price with profitability as intervening variable in banking companies listed in IDX (Indonesia Stock Exchange). The research used quantitative method. Secondary data were the companies’ financial statement, obtained from BEI in the period of 2013-2017. The population was 43 companies, and 29 of them were used as the samples, taken by using purposive sampling technique with the period of the research of 5 years so that there were 145 research units all together. The data were analyzed by using multiple linear regression analysis and path analysis with an SPSS statistic program. The result of the research showed that first, Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA) simultaneously had positive and significant influence on stock price. Second, VACA had positive and significant influence on stock price. Third, VAHU and STVA did not have any significant influence on stock price. Fourth, profitability was intervening variable in the influence of VACA and STVA on stock price, and fifth, profitability was not intervening variable in the influence of VAHU on stock price.